The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/plants11070873
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity of Potentilla paradoxa Nutt. and Its Beneficial Effects Related to Anti-Aging in HaCaT and B16F10 Cells

Abstract: Skin aging is a natural process influenced by intrinsic and extrinsic factors, and many skin anti-aging strategies have been developed. Plants from the genus Potentilla has been used in Europe and Asia to treat various diseases. Potentilla paradoxa Nutt. has been used as a traditional medicinal herb in China and has recently been shown to have anti-inflammatory effects. Despite the biological and pharmacological potential of Potentilla paradoxa Nutt., its skin anti-aging effects remain unclear. Therefore, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…Naringenin (67604-48-2, TCI), kaempferol (520-18-3, Sigma), genistein (446-72-0, TCI), apigenin (320-36-5, Sigma), hesperidin (520-26-3, Sigma), and rutin (153-18-4, Sigma) were used to create standard curves. GC-MS analysis of Lm-ME was carried out using the Cooperative Center for Research Facilities of Sungkyunkwan University (Suwon, Korea), as previously reported [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Naringenin (67604-48-2, TCI), kaempferol (520-18-3, Sigma), genistein (446-72-0, TCI), apigenin (320-36-5, Sigma), hesperidin (520-26-3, Sigma), and rutin (153-18-4, Sigma) were used to create standard curves. GC-MS analysis of Lm-ME was carried out using the Cooperative Center for Research Facilities of Sungkyunkwan University (Suwon, Korea), as previously reported [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…P. paradoxa Nutt. has been used as a medicinal plant in various regions since ancient times and many Cinquefoils (Potentilla) plants show anti-inflammatory effects [23,[25][26][27]. For this reason, we conducted a study on P. paradoxa Nutt.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the phytochemical components of Pp-EE, GC-MS/MS was conducted, as reported previously [25]. Based on the type of analysis component and the integration value in the graph of each component, the amount of content compared to the total amount was identified, and the contents were summarized.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms/ms)mentioning
confidence: 99%
See 1 more Smart Citation
“…The 15-LOX inhibitory activity of Gt-EE was determined according to the method described by Yasin et al with a slight modification [ 78 ]. In addition, 15-LOXs catalyze the reaction between linoleic acid and oxygen, producing 13-hydroperoxyoctadecadienoic acid that increases absorbance at 234 nm.…”
Section: Methodsmentioning
confidence: 99%